Pengaruh Penambahan Kulit Kayu Manis, Ketumbar dan Jintan Putih Terhadap Cita Rasa Rendang Daging Sapi Dengan Uji Hedonik - Savira Harna Febiyanti; Sherly Rahmayani; Taufik Maulana Rinata; Fitri Amelia; Iryani Iryani; Iswendi Iswendi (Jurnal Periodic Jurusan Kimia UNP, 2023)
Indonesia has many spices that have medicinal properties, one of which is cinnamon bark, coriander and cumin which are known to have antioxidants that can lower blood glucose levels, total cholesterol and anti-obesity. The purpose of this study was to determine the effect of cinnamon bark, coriander and cumin on the taste of beef rendang. The hedonic test was carried out with 15 panelists and the parameters observed were color, texture, aroma and taste. The results showed that the addition of cinnamon bark, coriander and cumin had no significant effect on texture, aroma and taste but significantly (P>0.05) on color organoleptic values.